Martín Fierro: " El destino de un canto" - Goldman, Marina; Escalona Toledo, Lucía (Nómadas. Critical Journal of Social and Juridical Science, 2013)
The aim of this paper is to analyze the debates about Martín Fierro as myth, as an exponent of Argentinean literature, and as a symbol of its patriotic ideal. We will consider the divergent interpretations and critiques of the poem by José Hernández, focused on the perspective of Carlos Astrata in "Mito gaucho" in opposition to Ezequiel Martínez Estrada in "Muerte y transfiguración del Martín Fierro". Our analysis will focus on three topics: the relationship between literature and national identity, the construction of Martin Fierro as a national masterpiece and its distinctive features within the gaucho literature, and the mythological character of this poem.